1994
DOI: 10.1677/joe.0.1410219
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin and follistatin concentrations in fetal tissues and fluids during gestation in sheep: evidence for activin in amniotic fluid

Abstract: The concentrations of inhibin and follistatin in amniotic fluid and in tissue extracts from the placenta, gonads and adrenals of fetal sheep were measured using radioimmunoassays. These tissue extracts were from whole fetuses from days 16 to 45 and from the individual organs from day 46 to 145 (term) and were assayed at multiple dilutions. The capacity of these extracts to alter FSH production of rat anterior pituitary cells in culture was also assessed at multiple dilutions. Immunoactive inhibin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…In contrast to the elevated concentrations observed in maternal plasma during pregnancy in the human, concentrations of ir-inhibin in the maternal plasma of the ewe are not elevated during late gestation apart from a transient rise observed at the time of parturition [4]. In this species the placenta does not appear to be a major source of inhibin since, although both bioactive and immunoactive forms of inhibin have been detected in the placenta during gestation [5], uninuclear trophoblast cells in culture produce only minimal amounts of inhibin [6], and there is no significant arteriovenous difference in ir-inhibin concentrations across the placenta in chronically cannulated late-pregnant sheep [7]. During pregnancy in both the human and sheep, no difference has been found in maternal plasma inhibin concentrations in individuals carrying male versus female fetuses [4,8].…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…In contrast to the elevated concentrations observed in maternal plasma during pregnancy in the human, concentrations of ir-inhibin in the maternal plasma of the ewe are not elevated during late gestation apart from a transient rise observed at the time of parturition [4]. In this species the placenta does not appear to be a major source of inhibin since, although both bioactive and immunoactive forms of inhibin have been detected in the placenta during gestation [5], uninuclear trophoblast cells in culture produce only minimal amounts of inhibin [6], and there is no significant arteriovenous difference in ir-inhibin concentrations across the placenta in chronically cannulated late-pregnant sheep [7]. During pregnancy in both the human and sheep, no difference has been found in maternal plasma inhibin concentrations in individuals carrying male versus female fetuses [4,8].…”
Section: Introductionmentioning
confidence: 56%
“…Both immunoactive and bioactive inhibin have been observed in high concentrations in ovine fetal testes throughout gestation [5]. Although bioactive and immunoactive inhibin were also observed in fetal ovaries and adrenals from both male and female fetuses, concentrations were lower than those observed in fetal testes.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We have previously shown that amniotic fluid from sheep contains predominantly activin bioactivity despite the fact that it contains elevated levels of immunoactive inhibin [9], and we subsequently isolated activin A [10] from a pool of this fluid. The placenta, fetal membranes, and maternal decidua have been shown to be sources of activin in human pregnancy [11][12][13][14], and there are preliminary data to suggest that activin A may be involved in parturition in humans [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that both activin ␤ A and ␤ B subunits are expressed in the amnion and chorion of humans [13]. Since we had previously shown that activin bioactivity was present in amniotic fluid, despite its high levels of immunoactive inhibin activity [9], and we were able to subsequently isolate activin A from amniotic fluid [10], we decided to investigate whether allantoic fluid also contained activin.…”
Section: Introductionmentioning
confidence: 99%